Inonotus obliquus fermentation product improves growth performance and meat quality probably through intestine and antioxidant capacity enhanced by gut microbes and metabolites regulation in rabbits - Lin Zhang; Zhiguo Fei; Yaling Ding; Yajia Zhang; Zhiyong Ding; Yueyan Huang; Junkun Wang; Gongyan Liu; Liya Bai; Jiaqiang Wu (Animal Microbiome)
Abstract Background Inonotus obliquus is a medicinal edible fungus that contains a variety of biologically active ingredients and has multiple physiological effects. When supplemented in avian diet, Inonotus obliquus has proved to be beneficial. However, information regarding these effects on mammals is scanty. The present study aims to investigate the effect of supplementation of Inonotus obliquus fermentation product (IOFP) on the growth performance, antioxidant capacity, meat quality, intestinal function and gut microbiota of rabbit exploratorily, which may act as an important feed additive and also as an antibiotic alternative with its medicinal properties. Results Dietary supplementation of IOFP increased body weight (P < 0.01) at the initial 21 d and improved feed efficiency throughout the 35 d experimental period when compared to control group. At the same time it was observed that meat quality and carcass parameters improved upon supplementation of IOFP. Additionally, IOFP supplementation resulted in significant increases (P < 0.05) in total antioxidant capacity (T-AOC), superoxide dismutase (SOD), and nitric oxide (NO) activity or concentration in the serum and muscle. The crypt depth decreased significantly, whereas the villus height/crypt depth (V/C) value increased (P < 0.05). The concentration of secrete IgA (sIgA) of the intestine also increased (P < 0.05). IOFP supplementation significantly increased the fold change expression of Claudin 1, Occludin, ZO1, and ZO2 (P < 0.05) when compared to the respective gene expression levels of the duodenum and jejunum tissues of control group. Further study on cecum microbiota revealed that IOFP supplementation increased the microbiota diversity by increasing the number of beneficial bacteria and reducing the numbers of pathological bacteria. It was observed that cecum metabolites produced in the treated group were related to antioxidants, antiinflammation and antidepressive effects. The harmful metabolites related to fat deposition, loss of appetite and cytotoxic conditions decreased. Pearson’s correlation studies between different bacteria and metabolites revealed that the metabolites produced were regulated by the beneficial and harmful bacteria respectively. Conclusions IOFP enhanced intestinal morphology and function, and organismic antioxidant capacity, probably by increasing the concentration of beneficial microbiota and metabolites resulting in improvement of body weight, feed efficiency, and parameters related to meat quality and carcass traits of rabbits. Graphical Abstract